Identification of risk- and preventive factors predicting child maltreatment in pregnant women with psychosocial problems - Ogawa, Michi; Hashimoto, Tasuku; Tanaka, Mami; Ishii, Hiroki; Seki, Ryota; Sato, Aiko; Kimura, Atsushi; Okayama, Jun; Endo, Mamiko; Saito, Naoki; Iyo, Masaomi (Frontiers in Psychiatry, 2025)
IntroductionPregnant women with psychosocial problems experience various parenting struggles, which, in the absence of adequate social support, can lead to child maltreatment. This study aimed to identify risk- and preventive factors for child maltreatment among pregnant women with psychosocial problems to facilitate the appropriate allocation of social support.MethodsThis retrospective cohort study analyzed electronic medical records of all consecutive pregnant women with psychosocial difficulties who visited and delivered at Chiba University Hospital, and were registered with the hospital’s child protection team between April 2016 and March 2019. The primary objective was to identify risk- and preventive factors associated with child maltreatment, defined as cases requiring intervention by a child guidance center. Multiple logistic regression analysis was performed to identify the risk factors and preventive factors influencing child maltreatment within the first month postpartum.ResultsA total of 253 pregnant women were included in the analysis, of whom 54 were reported for child maltreatment. Maternal grandmother’s support (OR: 7.85, 95%CI [3.47–17.77]) and other family members’ support (OR: 3.57, 95%CI [1.51–8.41]) were identified as preventive factors. Maternal mental illness (OR: 0.40, 95%CI [0.18–0.89]) was identified as a risk factor. Additionally, the higher the mother’s age (OR: 1.08, 95%CI [1.02–1.14]), the lower the incidence of child maltreatment, indicating that adolescent pregnancy is also a risk factor.ConclusionsFamily support, particularly from the maternal grandmother, plays a crucial role in enhancing parenting skills of women with psychosocial difficulties. Assessing these factors and integrating them into public support initiatives could contribute to the prevention of child maltreatment.